Survey on VoIP call security perception during COVID-19 pandemic - Taneska, Marija; Gramatikov, Sasho (My University, 2022)
The goal of this paper is to identify the most popular users' call security worries and users' perceptions about provided call security by popular VoIP-based applications during the COVID-19 pandemic. To accomplish this goal, we did a survey among different age categories in North Macedonia. In this paper, we describe how applications provide call security and we present and analyze the results of the survey.
Keywords: VoIP, security, COVID-19 pandemic